Diet composition, food intake, apparent digestibility, and body condition score of the captive Asian elephant (Elephas maximus): A pilot study in two collections in Thailand - Romain S. (American Association of Zoo Veterinarians, 2014)
Limited data are available regarding the nutrition and feeding of captive Asian elephants in range countries. In this study, feeding regimens of two collections in northern Thailand and their actual diets shaped by availability of forage and mahout preferences were assessed for nutritional quality. The composition of dietary intake, fecal output, and the dietary regimen were individually recorded for 5 days in 10 elephants. The proportion of forage in the diet represented 41 to 62% of the dry matter intake (DMI) in one collection whereas in the other collections it varied between 68 and 72%. Between 8.5 and 24% of the diet consisted of commercial pellets, and hulled rice represented up to 25% of the DMI in one collection. Sugar cane, corn cobs, and fruits such as bananas were eaten in smaller amounts. Body condition scores and weights were measured, which revealed that nine animals were in good condition. Representative samples of each food as well as fecal samples were analyzed for dry matter, crude protein, fat, crude fiber, gross energy, ash, calcium, and phosphorus. Diet adequacy was assessed by calculating the digestible nutrients in the rations and by comparing them to the recommendations from literature. The digestible energy (DE) intake varied between 0.6 and 1.4 megajoules (MJ) per kg0.75 per day; therefore, higher than the estimated recommendations of 0.65 MJ per kg0.75 per day for nine of the elephants. In all elephants the crude protein intake was less than the maintenance recommendations and ranged between 6.01 and 7.56% of the DMI. Calcium intake was low in one collection and there was an inverse calcium : phosphorus ratio, which was inadequate. The present study adds to the knowledge of captive elephant diets in Asia and is a starting point for further research, which is necessary to design optimum diet plans for captive Asian elephants in Thailand. © American Association of Zoo Veterinarians.